An Integrative Approach to Clinical Decision-Making for Treating Patients With Binge-Eating Disorder - Chyurlia, Livia; Tasca, Giorgio A.; Bissada, Hany (Frontiers in Psychology, 2019)
Transtheoretical integrative decision-making models help clinicians to use patient factors that are known to predict outcomes in order to inform individualized treatment. Patient factors with a strong evidence base include: functional impairment, social support and interpersonal functioning, complexity and comorbidity, coping style, level of resistance, and subjective distress. Among those with binge-eating disorder (BED), patient factors have not been extensively characterized relative to norms or other clinical samples. We used an integrative decision-making model of these six domains of patient factors related to patient outcomes to characterize a sample of 424 adult treatment-seeking patients with BED. Data were from medical charts, a demographics questionnaire, and validated psychometric scales. We then compared these data to published data from normative and other eating disorder (ED) samples. Results showed that the average patient with BED: (1) was significantly more functionally impaired compared to non-clinical norms but somewhat less impaired than other patients with ED, (2) demonstrated clinically significant problems in social support and interpersonal functioning, (3) presented with complex comorbid pathology and high levels of chronicity, (4) used a more internalizing coping style compared to the norm and other ED samples, (5) had low levels of resistance to interventions, and (6) experienced a moderately high level of subjective distress indicating good motivation for treatment. Corresponding recommendations to these findings are that the average patient with BED should be provided higher intensity treatment that is longer in duration, interpersonally-focused, directive in nature, and emphasizing self-reflection and insight. Despite the nomothetic nature of the findings, clinicians are encouraged to assess these patient domains in order to come to an ideographic case conceptualization and to tailor precision treatment to the individual patient with BED.